Recent French Export Performance. - Kabundi, Alain N. (IMF Working Papers., 2009)
Recently, the export performance of France relative to its own past and relative to a major trading partner, Germany, deteriorated. That deterioration seems related to the geographical destination and product composition of trend exports. Faced with an increase in unit labor costs or in its terms of trade, France adjusts relatively less via price and wage changes, and more via employment changes. Given that SMIC convergence resulted in a significant increase in unit labor costs, foreign sector difficulties might be structural. Trade flows relevance and euro area policy constraints highlight th.